Gandhi Before India - Ramachandra Guha (Allen Lane / Penguin Books, 2013)
In 1893, when Mohandas Gandhi set sail for South Africa, he was a twenty three year old brief less lawyer who failed to establish himself in India. In this remarkable Biography, Ramchandra Gotha argues that the two decades that Gandhi spent in South Africa were to be the making of the Mahatma. It was there that he came to understand the nature of imperialism and racism and it was there that he forged the philosophy and techniques that would ultimately destroy the British Empire.Based on a wealth of new material, Gandhi before India paints a vivid portrait of Gandhi and the world he lived in. It explores in detail his experiments with dissident cults such as the Theosophists and vegetarians, his friendship and enmities and his failures as a husband and a father. It also tells the dramatic, deeply moving story of how he mobilized a cross-class, inter-religious coalition of devoted followers pledged to non-violence, who joined him in battling South Africa's brutally racist regime.Deeply researched and beautifully written, this book will radically alter our understanding and appreciation of Mahatma Gandhi.